Isoacid supplementation influences feed sorting, chewing behaviors, and enteric methane emissions differentially in mid-lactation dairy cows depending on dietary forage level - M.R.A. Redoy; S. Ahmed; M. Bulnes; D.H. Kleinschmit; M.E. Uddin (Journal of Dairy Science)
ABSTRACT: Past studies have shown that isoacids (ISO) improve dairy cow performance, with effects varying based on dietary forage levels, leading us to speculate that ISO supplementation may also differentially affect enteric methane (CH4) emissions depending on dietary forage levels. Therefore, our primary objective was to examine the effects of ISO supplementation on enteric CH4 emissions in lactating dairy cows fed 2 forage NDF levels (FL), along with monitoring feed particle sorting and chewing behaviors to assess any potential interactions. Sixty-four mid-lactation Holstein cows were used in a 10-wk long randomized complete block design trial. Parity, DIM, and prior milk yield (MY) for multiparous cows or genetic merit for primiparous cows were used as blocking factors. Cows were randomly assigned to 1 of 4 diets (n = 16 per diet) with a 2 × 2 factorial arrangement of treatment combinations, including 2 FL, 17% (LF) and 21% forage NDF (HF), without or with ISO supplementation (7.85 mmol/kg DM for isobutyrate and 3.44 mmol/kg DM for 2-methylbutyrate, respectively). Enteric CH4 and chewing activity (rumination and eating time) were measured using the GreenFeed system and sensor-based ear tag system, respectively. The particle size of each diet and ort from individual cows was measured using the Penn State Particle Separator, and a sorting index was calculated. A sorting index of 100 indicates no sorting, whereas values above or below 100 indicate sorting for or against, respectively. Data were analyzed using a mixed model including FL, ISO, and FL × ISO as fixed effects and block as a random effect (lme4 in R). Our result shows that ISO increased sorting index for long particle in LF (96.1 vs. 109; P < 0.01) but decreased it in HF (100.8 vs. 92.5; P = 0.04). In contrast, ISO did not affect the physically effective particle sorting index (P = 0.51) or intake (P = 0.27) regardless of FL. In alignment with the long particle sorting index, ISO decreased eating and chewing time in the HF but increased them in the LF diet (P < 0.01). In contrast, rumination time was comparable between FL (P = 0.70) and ISO levels (P = 0.19). In the LF diet, ISO supplementation reduced daily CH4 production (g/d) by 9% and intensity (g/kg of MY) by 18% (P < 0.01). In the HF diet, ISO supplementation led to a 10% increase in daily CH4 (P < 0.01) but did not change CH4 intensity (P = 0.17; g/kg of MY) due to improved milk production. Overall, ISO altered feed sorting, feeding behaviors and enteric CH4 emissions depending on FL.